Penaksiran Laba Pada Akuntansi UMKM Via Online di Kabupaten Sumenep - Leily Nur Indah Fitriana; Rohmaniyah (AKUA: Jurnal Akuntansi dan Keuangan, 2022)
MSME actors in Sumenep Regency generally have not implemented the separation between business entities and private entities so that measuring profits is not in accordance with SAK EMKM. Currently, MSME in Sumenep Regency market their products using social media and sell directly. Talking about the birth of accounting, accounting practices were born with business practices, therefore there is a change from traditional business practices to online so that all accounting practices are changed. This research is a qualitative descriptive study that uses primary data by conducting interviews with correspondents with the technique of describing the data discussed with existing theories and conclusions will be drawn. The population of this study is some MSME in Sumenep Regency who market their products online with a random sample of 13 MSME actors. The results of this study resulted in online MSME profit measurements using varied and simple accounting practices.